Rough turning of titanium alloy (6Al-4V) - Ribeiro, Marcos V. [UNESP]; Moreira, Marcos R.V.; Ferreira, Joäo R. (My University, 2012)
Metal machining is the complex process due the used cutting parameters. In metal cutting process, materials of workpiece differ widely in their ability to deform plastically, to fracture and to sustain tensile stresses. Moreover, the material involved in the process has a great influence in these operations. The Ti-6Al-4V alloy is very used in the aeronautical industry, mainly in the manufacture of engines, has very important properties such the mechanical and corrosion resistance in high te mperatures. The turning of the Ti-Al-4V alloy is very difficult due the rapid tool wear. Such behavior result of the its low thermal conductivity in addition the high reactivity with the cutting tool. The formed chip is segmented and regions of the large deformation named shear bands plows formed. The machinability of the cutting process can be evaluated by several measures including power consume, machined surface quality, tool wear, tool life, microstructure and morphology of the obtained chip. This paper studies the effect of cutting parameters, speed and feed rates, in the tool wear and chip properties using uncoating cemented carbide tool. Microe-structural characterization of the chip and tool wear was performed using scanning electron microscopy (SEM) and Light Optical Mcroscopy (LOM).
Keywords: Shear band; Titanium (Ti) machining; Wear; Cemented carbide tools; Complex Processes; Cutting parameters; High reactivity; Low thermal conductivity; Machined surface quality; Metal cutting process; Metal machining; Aluminum; Corrosion resistance; Cutting tools; Metal cutting; Scanning electron microscopy; Shear bands; Turning; Wear of materials; Titanium alloys